Analisis Sensitivitas Cadangan Prospektif Asuransi Jiwa Seumur Hidup terhadap Fluktuasi BI-Rate Berdasarkan Tabel Mortalitas Indonesia IV - Meisyy Laisa Usrini Deswan; Hafizha Zahra; Aulia Kusuma Putri (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
This study aims to analyze the sensitivity of prospective reserves for whole life insurance to BI-Rate fluctuations based on the Indonesian Mortality Table (TMI) IV. The method used is quantitative, using secondary data in the form of a male population in TMI IV, assuming a certain entry age, a fixed sum insured, and a fixed annual premium. Three constant interest rate scenarios are applied: pessimistic, normal, and optimistic. Prospective reserves are calculated using the gross premium valuation method using commutation symbols. The results show that a decrease in interest rates significantly increases reserves, especially at the middle of the policy life, and results in a positive initial reserve indicating an immediate liability burden. Conversely, an increase in interest rates depresses reserves to a negative value, reflecting a capital surplus. The conclusion of this study is that BI-Rate fluctuations significantly impact the solvency of life insurance companies, necessitating a dynamic asset-liability matching strategy.